Pemetaan Potensi Wilayah Sebagai Peluang Investasi Dalam Pengembangan Ekonomi di Kabupaten Luwu Timur - Muh. Ibnu Fauzi Akbar; Kamran Aksa; Ilham Yahya; Nani Anggraini (Fakultas Teknik Universitas Bosowa, 2023)
This study aims to determine the potential mapping region for investment opportunities. This research is a quantitative research for consideration as well as reference material in analyzing descriptively. which variable used include mapping the potential of the area and investment opportunities. The analytical method used is LQ analysis, in determining commodity sector base and potential sector. Based on the results of the LQ analysis, it produces Regional Potentials, among others Agriculture, Plantation, Animal Husbandry, Fisheries and Marine Sectors, and Mining.